Need for the Development of Dialectical Thinking in Pharmaceutical Personnel to Improve Their Performance in the Pharmacovigilance System - A. E. Krasheninnikov; B. K. Romanov; R. S. Safiullin; N. V. Shestakov (Безопасность и риск фармакотерапии, 2022)
The pharmacovigilance system aimed at ensuring the safety of medicines has been functioning in Russia since 1997. However, at the moment, an important part of this system, pharmacy organisations, is not sufficiently involved in pharmacovigilance activities. Pharmacy personnel may be not prepared to collect information on adverse reactions associated with the use of medicinal products and submit it to regulatory authorities. The reason is not only that their knowledge of pharmacovigilance is insufficient, but also that little attention is paid in the educational process to the development of dialectical thinking, which is necessary for successful problem-solving. The available literature does not cover the importance of dialectical thinking as a professional competency of a pharmacy employee sufficiently well.The aim of the study was to substantiate the need in the development of dialectical thinking in employees of pharmacy organisations in order to increase their participation in the pharmacovigilance system.Materials and methods: 166 employees of pharmacies in Kazan were surveyed on the implementation of pharmacovigilance in pharmacy organisations. The authors used Spearman’s rank correlation coefficient to assess the extent of association between the variables identified in the survey (pharmacy’s standing in the pharmacovigilance system, respondents’ competence in pharmacovigilance, their familiarity with pharmacovigilance documentation, adverse reaction reporting, and so forth).Results: the majority of respondents perceive the importance of pharmacies for the pharmacovigilance system as medium (46.99%) and low (17.47%); the same is true for the level of pharmacovigilance development in pharmacies (45.63 and 27.5% of the respondents respectively). According to the correlation analysis, pharmacy employees do not associate the level of pharmacovigilance development in their pharmacy with their competence, which is characteristic of a dialectical failure. Most respondents tend to exaggerate the role of executive authorities, medical organisations, and pharmaceutical companies in the pharmacovigilance system and underestimate the role of pharmacies and pharmacy staff (only 17.62% of the respondents assign this role to pharmacies), which may be the reason for failing to fulfil pharmacovigilance duties and passing the responsibility to other parties to the circulation of medicinal products.Conclusions: according to the consolidated results, pharmacy employees may not consider themselves to be leading implementers of legislative initiatives, causally related to the effectiveness of pharmacovigilance system as a whole. Consequently, there is a need to form dialectical thinking in pharmacy employees within the framework of educational programmes. It will contribute to the development of reflection on their efforts in ensuring the safety of medicines and increase the effectiveness of their participation in pharmacovigilance activities.